The effects of (incentivized) belief elicitation in public goods experiments - Simon Gächter; Elke Renner (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2010)
Belief elicitation is an important methodological issue for experimental economists. There are two generic questions: 1) Do incentives increase belief accuracy? 2) Are there interaction effects of beliefs and decisions? We investigate these questions in the case of finitely repeated public goods experiments. We find that belief accuracy is significantly higher when beliefs are incentivized. The relationship between contributions and beliefs is slightly steeper under incentives. However, we find that incentivized beliefs tend to lead to higher contribution levels than either non-incentivized beliefs or no beliefs at all. We discuss the implications of our results for the design of public good experiments.
Keywords: C90; 330; incentives; beliefs; experimental methodology; public goods; Ökonomischer Anreiz; Meinung; Entscheidung; Öffentliches Gut; Test